Hubungan antara Sense of Self (SOS) dengan Perilaku Merokok pada Siswa Laki-laki di SMK Negeri di Kabupaten Jember - Febria Savitry Arum Melati; Emi Wuri Wuryaningsih; Enggal Hadi Kurniyawan (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
The prevalence of smoking behavior in adolescents tends to be high and increases from year to year. Generally, adolescents know about the negative effects of smoking behavior, but they do not want to stop. It is related to the low feeling about himself or his sense of self (SOS). The study analyzed the correlation between a sense of self (SOS) and smoking behavior. The study used an observational cross-sectional approach. The population involved were male students in State Vocational Schools in Jember Regency amounted to 2,590, which was then calculated using the proportionate stratified random sampling technique (CI: 95%) and respondents were 209. The research instrument uses a modification of The Sense of Self Scales (α-Cronbach = 0.05; 11 question items) and smoking behavior questionnaire (α-Cronbach = 0.05; 21 question items). Statistical tests using the Spearman Rank Test (CI: 95%; α <0.05). The ethics of this study was given by the Nursing Ethics Commission (KEPK) FKG Jember University with the number: No. 643/UN25.8/KEPK/DL/2019. The results showed 75.59% (active smokers) and 24.41% (not smoking) adolescent sense of self (SOS) towards smoking behavior (Med: 17.00 with a value of min 2 and max 30; CI: 95%). The higher the sense of self (SOS) of adolescents, the teenage boys tend to avoid smoking behavior (p = 0,000; α <0.05; r = -0.665). Factors that can affect adolescent behavior are external and internal. Teenagers need a situation that peers can accept, so peers become an important influential factor. However, the most influential factor on a teenager's decision-making is internal factors, one of which is the sense of self (SOS). As community nurses, we must be able to promote and prevent of smoking behavior through efforts to increase adolescent's sense of self.